Gastric Cancer Stem Cells Effect on Th17/Treg Balance; A Bench to Beside Perspective - Rezalotfi, Alaleh; Ahmadian, Elmira; Aazami, Hossein; Solgi, Ghasem; Ebrahimi, Marzieh (Frontiers in Oncology, 2019)
Gastric cancer stem cells (GCSCs), a small population among tumor cells, are responsible for tumor initiation, development, metastasis, and recurrence. They play a crucial role in immune evasion, immunomodulation, and impairment of effector immunity and believed to be emerged to change the balance of the immune system, importantly CD4+ T cells in the chronic inflamed tumor site. However different subtypes of innate and adaptive immune cells are involved in the formation of the immune system in the tumor microenvironment, we would look at T cells in this study. Tumor microenvironment induces differentiation of CD4+ T cells into different subsets of T cells, mainly suppressive regulatory T cells (Treg) and T helper 17 (Th17) cells, although their exact role in tumor immunity is still under debate depending on tumor types and stages. Counterbalance between Th17 and Treg cells in the gastrointestinal system result in the homeostasis and normal function of the immune system, particularly mucosal immunity. Recent data demonstrated a high infiltration of Th17 and Treg cells into the gastric tumor site and proved that tumor microenvironment might disturb the balance between Th17 and Treg. It is possible to assume an association between activation of CSCs which contribute to metastasis in late stages, and the imbalanced Th17/Treg cells observed in advanced gastric cancer patients. This review intends to clarify the importance of gastric tumor microenvironment specifically CSCs in relation to Th17/Tregs balance firstly and to highlight the relevance of imbalanced Th17/Treg subsets in determining the stages and behavior of the tumor secondly. Finally, the present study suggests a clinical approach looking at the plasticity of T cells with a focus on Th17 as a promising dedicated arm in cancer immunotherapy.